Análisis del impacto de la transición demográfica en el mercado laboral en la ciudad de Bogotá para los sectores de servicio y comercio entre los años 2020,2030,2040 y 2050. (2023)
This work aims to analyze the impact of the demographic transition on the labor market in the city of Bogotá, specifically in the service and commerce sectors, during the years 2020, 2030, 2040 and 2050. Through the analysis of demographic indicators and the Comparison of historical trends and projections will seek to identify the challenges and opportunities that the demographic transition presents in terms of employability. The results of this study will provide valuable information for the formulation of policies and strategies that promote equality and labor inclusion in the city of Bogotá, thus promoting sustainable and equitable economic development in the future.